Implementation of a Web based System and Mobile Platform for Encouragement of Local People to Engage in Proper Workout Practices Such that Ensuring their Health and Physical Wellbeing Stays on Good Standards - Siriwardana, M.G.G.K.H.; Sandeepa, U.W.P.S.; Amarakoon, A.R.W.M.M.L.O.; Weerasinghe, R.B.; D.I. De Silva; R.R.P. De Zoysa (International Journal of Engineering and Management Research, 2022)
Improperly maintained unhealthy livelihood of a person will have a direct impact on his or her life and as well as safety. When it comes to good health and wellbeing, there is nothing which comes above that. Careless and unreliable guidelines on workout postures, not knowing about compulsory nutrients for body and the poor knowledge on supplements are the major reasons behind most of the people being the bearers of fatty, lethargic bodies surrounded with diseases. It is better to know the thing in the correct way and practice it, rather than engaging in it without knowing the consequences and benefits. A system will be proposed to collaborate with the well experienced trainers, coaches and physicians in nationwide to provide proper health guidelines to have good food, better postures on workouts and ultimately a healthy body with no worries about deadly diseases. Likewise, a web application which brings up the blog posts on the tips and informative guidelines on a healthy life which is mutually collaborated with a mobile application to track the users on following those guidelines properly would be the ideal solution for a country to enhance their health standards in a progressive way.